2009
DOI: 10.1016/j.aquaculture.2009.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla protein in turbot (Scophthalmus maximus): Gene expression analysis and identification of sites of protein accumulation

Abstract: Matrix Gla protein (Mgp) is a secreted vitamin K-dependent extracellular matrix protein and a physiological inhibitor of calcification whose gene structure, amino acid sequence and tissue distribution have been conserved throughout evolution. In the present work, the turbot (Scophthalmus maximus) mgp cDNA was cloned and the sequence of the deduced protein compared to that of other vertebrates. As expected, it was closer to teleosts than to other vertebrate groups but there was a strict conservation of amino-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…Although no morphological difference was seen in the notochordal tissue between control and hypervitaminosis A fed fish, immunohistochemical analysis revealed higher levels of MGP and OC, which are considered as chondrogenic and osteoblastic biomarkers. MGP protein accumulation in the notochordal tissue was in agreement with previous described pattern in different fish species (Gavaia et al., 2006; Roberto et al., 2009), which seemed to prevent local calcification (Roberto et al., 2009). However, OC protein distribution in the notochordal tissue was not found in Solea senegalensis larvae (Gavaia et al., 2006), although it has been shown a high mRNA OC expression in the vertebra by Northern blotting and in notochordal tissue by in situ hybridization in gilthead sea bream (Pinto et al., 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Although no morphological difference was seen in the notochordal tissue between control and hypervitaminosis A fed fish, immunohistochemical analysis revealed higher levels of MGP and OC, which are considered as chondrogenic and osteoblastic biomarkers. MGP protein accumulation in the notochordal tissue was in agreement with previous described pattern in different fish species (Gavaia et al., 2006; Roberto et al., 2009), which seemed to prevent local calcification (Roberto et al., 2009). However, OC protein distribution in the notochordal tissue was not found in Solea senegalensis larvae (Gavaia et al., 2006), although it has been shown a high mRNA OC expression in the vertebra by Northern blotting and in notochordal tissue by in situ hybridization in gilthead sea bream (Pinto et al., 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Although turbot metamorphosis is currently well described and the central role of thyroid hormone (THs) in this process is well established (Power et al, 2008;Infante et al, 2008;Roberto et al, 2009), there is no evidence for a putative regulatory role of THs on sparc expression. However, a number of different factors, such as parathyroid hormone (PTH; Nakajima et al, 2002) and dexamethasone (Sawhney, 2002), have been shown to regulate sparc and indicate that it might be an important intermediate in hormone action.…”
Section: Discussionmentioning
confidence: 98%
“…This metamorphic remodeling is characterized by several drastic physiological changes that involve a high active remodeling in different organs, such as skin (Campinho et al, 2007), the musculo-skeletal system (Saele et al, 2006), nervous system (Graf and Baker, 1990) and intestinal system (Tanaka et al, 1996). Although, turbot metamorphosis is now well described and the central role of thyroid hormone in this process is well established (Power et al, 2008;Infante et al, 2008;Roberto et al, 2009), few data are available concerning the regulation of potential specific target genes in the context of the gene network responsible for metamorphic remodeling of larval tissues. During metamorphosis, a significant number of transcription factors and developmental genes have a regulated expression, and it has specifically been shown that in the late stages of remodeling, genes that are necessary for cell proliferation, signal transduction, and cell-cell signaling are significantly upregulated (Kulkarni and Buchholz, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…This protein is an inhibitor of soft-tissue calcification in mammals [47] and its expression in soft tissues from teleost fish suggests a conservation of that function [48][49][50]. MGP is generally associated with the organic matrix of cartilage and bone in vivo in both mammals and fish [50][51][52]. In ABSa15 cells, as well as in other fish bone-derived cells [22], MGP is also a marker for ECM mineralization [20], and therefore its increase in cells overexpressing miR-29a is in agreement with the associated phenotype.…”
Section: Mir-29a Promotes Ecm Mineralizationmentioning
confidence: 98%
“…Another remarkable effect was an up-regulation of mgp expression, which was also likely to be indirect. This protein is an inhibitor of soft-tissue calcification in mammals [47] and its expression in soft tissues from teleost fish suggests a conservation of that function [48][49][50]. MGP is generally associated with the organic matrix of cartilage and bone in vivo in both mammals and fish [50][51][52].…”
Section: Mir-29a Promotes Ecm Mineralizationmentioning
confidence: 99%